Kesantunan Berbahasa Tuturan Suami Istri Keluarga Banjar: Tinjauan Sosiopragmatik - NFN Jahdiah (Balai Bahasa Provinsi Riau, 2019)
Language politeness does not only occur in the society, but it also occurs in a close society that is family. Family is the smallest society. It is formed because of blood relationship and marriage like husband and wife. This study aims to describe politeness language between husband and wife in Banjar family. The method used in this study is descriptive method. To get qualitative descriptive, this study applies three steps, they are: providing the data, analysing the data, and presenting the result. The result shows that there are collision toward the principal politeness language of husband and wife utterance in Banjar family, collision toward 1) agreement maxim, 2) sympathy maxim, 3) approbation maxim, and 4) tact maxim. There are also politeness principal applies in husband and wife utterance, the application of 1) approbation maxim, 2) agreement maxim, 3) generosity maxim, and 4) sympathy maxim.